Positive effect of Bifidobacterium animalis subsp. lactis VHProbi YB11 in improving gastrointestinal movement of mice having constipation - Cui, Hongchang; Wang, Qian; Feng, Congrui; Guo, Chaoqun; Zhang, Jingyan; Bu, Xinping; Duan, Zhi (Frontiers in Microbiology, 2022)
The aim of this study was to investigate the effects of Bifidobacterium animalis subsp. lactis VHProbi® YB11 (YB11) on attenuating sucralfate-induced constipation in BALB/c mice. The strain of YB11 exhibited favorable tolerance of simulated gastrointestinal (GI) juice and the ability to adhere the intestinal epithelium Caco-2 cells. Mice were randomized into four groups. The normal group (NOR) was fed a normal diet, whereas the placebo group (PLA), positive group (POS), and probiotic group (PRO) were fed sucralfate to induce constipation. The NOR and PLA groups were orally administered saline solutions after first successfully establishing the constipation model. Meanwhile, the POS and PRO groups were orally administered phenolphthalein and YB11 suspensions, respectively. Several indices, including fecal water content, GI transit time, short-chain fatty acids (SCFAs), intestinal neurotransmitter levels, and histopathology of colonic tissues, were investigated. Compared with PLA, YB11 had a positive effect in increasing the fecal water content and intestinal peristalsis, and the acetate and total acid levels of fecal samples were also increased and the colonic tissue damages decreased. Furthermore, YB11 had an ability to upregulate the levels of gut excitatory hormones including motilin, gastrin, and substance P, whereas it downregulated the levels of inhibitory hormones including endothelin-1, somatostatin, and vasoactive intestinal peptide. We conclude that the strain YB11 has a positive impact in improving gastrointestinal mobility and reducing the severity of constipation.